Evaluation of the effect of kidney transplantation on left ventricular myocardial work by noninvasive pressure-strain loops - Han, Zhengyang; Wang, Lingyun; Wang, Honghu; He, Hongying; Song, Yi; Wang, Menghe; Zhao, Na; Chen, Zhengguang; Sun, Zhenxing; Zhang, Shan (Frontiers in Cardiovascular Medicine, 2024)
Purpose Kidney transplantation (KT) has the potential to reverse the cardiac changes caused by end-stage renal disease, and it may be inaccurate to analysis the left ventricular function by conventional echocardiography due to afterload. This study aimed to investigate the utility of pressure strain loops (PSLs) in evaluating left ventricular performance in patients underwent KT. Methods We enrolled 60 patients with end-stage renal disease who underwent KT between January 2022 and July 2023, and 60 healthy controls with a similar distribution of gender and age to the patients. All participants underwent conventional echocardiography and three-dimensional speckle tracking echocardiography (3D-STE). Long axis, short axis, and four cavity images were collected and cardiac parameters were measured. The echocardiographic changes of cardiac structure and function of all patients before KT and about 12 months after KT were recorded. Left ventricular myocardial work parameters were acquired by PSLs, including the global work index (GWI), global constructive work (GCW), global wasted work (GWW), global work efficiency (GWE) and global longitudinal strain (GLS). In addition, the correlation between PSLs and clinical data were explored. Results Compared with controls, the conventional echocardiographic parameters, myocardial function indicators GWI and GCW appeared no difference in post-KT group, while the GWE and GLS decreased (p < 0.05), and the GWW increased (p < 0.05). Compared with pre-KT, the GLS, GWI, GCW and GWE increased in post-KT group, while the GWW decreased (all p < 0.05). The above indicators were correlated with left ventricular GLS and left ventricular ejection fraction. Conclusion PSLs were more sensitive than traditional echocardiographic indicators in detecting changes in myocardial work and predicting left ventricular myocardial damage. This indicator could quantitatively evaluate myocardial work and provide a new and reliable non-invasive reference for clinical diagnosis and treatment of patients underwent KT.